Efficacy of individualized orelabrutinib-based regimens in relapsed or refractory central nervous system lymphoma - Yuchen Wu; Xuefei Sun; Liwei Lv; Qu Cui; Jun Qian; Ruixian Xing; Xueyan Bai; Yuedan Chen; Qing Liu; Wenyuan Lai; Chunji Gao; Shengjun Sun; et al. (Frontiers in Neurology)
BackgroundRelapsed or refractory central nervous system lymphoma (rrCNSL) lacks established preferred treatment and carries an inferior prognosis. Bruton’s tyrosine kinase inhibitor (BTKi) showed promising effectiveness. Orelabrutinib is a second-generation BTKi with a high concentration in cerebrospinal fluid.MethodsIn this retrospective analysis, the outcomes of 37 relapsed or refractory central nervous system diffuse large B-cell lymphoma patients who received orelabrutinib, high-dose methotrexate, ifosfamide, etoposide, and dexamethasone (Ore-MIED) or orelabrutinib, high-dose methotrexate, temozolomide and dexamethasone (Ore-MTD) were evaluated.ResultsOf the 37 patients included, 11 received Ore-MTD, and 26 received the Ore-MIED regimen. The overall response rate in our cohort was 89.2%, with complete remission achieved in 51.4% of patients and partial remission in 37.8% of patients. The median progression-free survival was observed to be 7.0 months. No statistically significant difference was found in the median progression-free survival between patients receiving different treatment regimens (5.0 months for Ore-MTD versus 13.0 months for Ore-MIED; p = 0.29). Moreover, the median overall survival has not been reached in this cohort, indicating a promising outcome despite the aggressive nature of the disease.ConclusionOur study confirms the effectiveness and safety of Ore-MIED/Ore-MTD in rrCNSL patients, even in those with previous exposure to multiple lines of treatment.